2022
DOI: 10.1051/0004-6361/202141684
|View full text |Cite
|
Sign up to set email alerts
|

From the Circumnuclear Disk in the Galactic Center to thick, obscuring tori of AGNs

Abstract: The high accretion rates needed to fuel the central black hole in a galaxy can be achieved via viscous torques in thick disks and rings, which can be resolved by millimeter interferometry within the inner ∼20 pc of the active galaxy NGC 1068 at comparable scales and sensitivity to single dish observations of the Circumnuclear Disk (CND) in the Galactic Center. To interpret observations of these regions and determine the physical properties of their gas distribution, we present a modeling effort that includes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…However, we note that these parameters undergo a multidimensional transformation because not only will the velocity dispersion 〈v 2 〉 differ for the single objects inside of the cluster depending on their global habitat (CND and inner parsec), but also the impact parameter Λ will change due to the ongoing dissolution of IRS 13. In addition, the number density between the CND and inner parsec increases by almost 100% (Vollmer et al 2022) which should result in a decreased orbital energy (Zajaček et al 2017), which we mimic by setting v virial to 10% as soon as the cluster enters the NSC. Based on these settings, we show in Figure 7 the snapshots for a cluster with different numbers of particles moving toward the inner parsec at 0.1 Myr and 0.2 Myr.…”
Section: N-body Simulationsmentioning
confidence: 99%
“…However, we note that these parameters undergo a multidimensional transformation because not only will the velocity dispersion 〈v 2 〉 differ for the single objects inside of the cluster depending on their global habitat (CND and inner parsec), but also the impact parameter Λ will change due to the ongoing dissolution of IRS 13. In addition, the number density between the CND and inner parsec increases by almost 100% (Vollmer et al 2022) which should result in a decreased orbital energy (Zajaček et al 2017), which we mimic by setting v virial to 10% as soon as the cluster enters the NSC. Based on these settings, we show in Figure 7 the snapshots for a cluster with different numbers of particles moving toward the inner parsec at 0.1 Myr and 0.2 Myr.…”
Section: N-body Simulationsmentioning
confidence: 99%
“…For instance, Shin et al ( 2021 ) showed that although NGC 1068 is known to have gas outflows originating from its AGN, more complex kinematical signatures have recently been detected that are in conflict with rotating outflows or simple biconical outflows. Vollmer et al ( 2022 ) applied the analytical model of a turbulent clumpy gas disc of Vollmer & Davies ( 2013 ) to produce an NGC 1068 dynamical model that could reproduce the high spatial resolution ALMA CO, HCO + , and HCN observations of the nucleus of NGC 1068. They find that the simplest configuration that can explain the kinematics of NGC 1068 is that of infalling gas clouds into a pre-existing gas ring and that the best-fitting cloud-ring collision is prograde for the CND and retrograde for the NGC 1068.…”
mentioning
confidence: 99%